Application of continuous quality improvement in promoting the cooperative development of district-level Central Sterile Supply Department (持续质量改进在促进区级消毒供应中心合作发展中的应用) - SONG Gang (宋钢); MA Qiong (马琼); DUAN Yanxiang (段艳香) (中西医结合护理)
Objective To explore the application effect of continuous quality improvement (CQI) in promoting regional cooperation and development of district-level Central Sterile Supply Department (CSSD). Methods The CQI program had been carried out based on the cooperative development of district-level Central Sterile Supply Department science 2020. The quality of cleaning and disinfection of medical apparatus package collected from district-level CSSD was evaluated before and after implementation of CQI. The knowledge level and satisfaction of nursing staff from district-level CSSD were assessed. Results The rates of qualified preprocessing, cleaning, packaging and storage in CSSD after implementation of CQI were higher than those before implementation of CQI(P＜0. 01). The rate of CSSD-related knowledge mastery and total satisfaction rate after the implementation of CQI were higher than those before implementation of CQI (P＜0. 01). Conclusion The application of CQI in the management of district-level Central Sterile Supply Department can ensure the quality of equipment cleaning and sterilization, improve the work efficiency and the overall level of infection prevention and control of medical institutions in the region. (目的 探讨持续质量改进(CQI)在促进区级消毒供应中心区域合作发展的应用效果。方法 2020年度基于医院的区域化消毒供应中心实施CQI管理。分别于CQI实施前和实施后抽取各合作基层医疗机构送至医院消毒供应中心再处理物品240件, 比较2019年1月—12月(实施前)及2020年1月—12月(实施后)消毒供应中心器械管理质量, 评价区域化消毒供应涉及医护人员消毒供应理论水平和满意度情况。结果 CQI实施后消毒供应中心器械预处理合格率、清洗合格率、包装合格率、存储合格率均高于实施前, 差异有统计学意义(P＜0. 01)。CQI实施后医护人员对消毒供应理论知识及流程掌握度及满意度均较CQI实施前提升, 差异有统计学意义(P＜0. 01)。结论 在区级消毒供应中心管理中应用CQI, 可以确保器械清洗、灭菌质量, 提高工作效率, 整体提升区域内医疗机构感染防控水平, 确保患者安全。)